Studying the properties of solidified oil-contaminated soil by magnesium oxychloride cement - Jiling Liang; Xianjin Zheng; Lu Wang; Guangdi Zhong; Guang Lu (Scientific Reports)
Abstract Magnesium oxychloride cement (MOC) has been used to solidify oil-contaminated soil (OCS) in order to reuse the OCS in civil construction. Several factors such as the mass ratio (R W/S) of liquid to solid, oil-contaminated soil dosage (D S), and the oil content (W o) of OCS were investigated to obtain the appropriate solidifying parameters for improving the unconfined compression strength (R C) of the obtained MOC-solidified oil-contaminated soil blocks (labeled as MS). To further optimize the R C, varying concentrations (D n) of Na2SiO3 aqueous solution and fly ash were added to the MS. Suitable D n and fly ash dosage (D f) improved the R C. Representative samples of MS8, MS10, MS14 and MS15 were used to perform water resistance tests for 14 days in water having different pH values at 25.0 ºC. Compared to the acidic pH range of 2.5-6.0, the water resistance was better in the alkaline pH range of 7.0～9.0 and was found to reduce with increasing time. Addition of Na2SiO3 impaired water resistance. However, addition of fly ash hardly affected the water resistance. Interestingly, more than 90% organics was immobilized in MS and the TOCL in the lixivium was less than 5 mg·L-1 for optimized MS.